Estimation of the Largest and the Smallest Function Values of a Feasible Solution for the Total Product Rate Variation Problem - Khadka, Shree Ram (Journal of Institute of Science and Technology, 2015)
The problem of minimizing the total deviations between the actual and the ideal cumulative production of a variety of models of a common base product arises as a sequencing problem in mixed-model just-in-time production systems. This is called the total product rate variation problem. Several pseudo-polynomial exact algorithms and heuristics have been derived for this problem. In this paper, we estimate the largest and the smallest function values of a feasible solution for the problem when the m-th power of the total deviations between the actual and the ideal cumulative productions has to be minimized Journal of Institute of Science and Technology, 2014, 19(1): 35-38